Plasma Procalcitonin Concentration in Healthy Horses and Horses Affected by Systemic Inflammatory Response Syndrome. (16th October 2015) - Bonelli, F.; Meucci, V.; Divers, T.J.; Jose‐Cunilleras, E.; Corazza, M.; Tognetti, R.; Guidi, G.; Intorre, L.; Sgorbini, M.
Abstract : Background: The diseases most frequent associated with SIRS in adult horses are those involving the gastrointestinal tract. An early diagnosis should be the goal in the management of horses with SIRS. Objective: The objective of this study was to evaluate the plasma procalcitonin (PCT) concentration in healthy and SIRS horses to assess differences between the two groups. Animals: Seventy‐eight horses (30 healthy and 48 SIRS). Methods: Prospective in vivo multicentric study. Horses were classified as SIRS if at least 2 of the following criteria were met: abnormal leukocyte count or distribution, hyperthermia or hypothermia, tachycardia, tachypnea. Healthy horses showed no clinical or laboratory signs of SIRS. Plasma PCT concentrations were measured with a commercial ELISA assay for equine species. Results were expressed as mean±standard deviation. T‐test for unpaired data was performed between healthy and SIRS group. SIRS group was divided in 4 subgroups and t ‐test was performed between healthy versus each subgroup. Results: PCT concentrations in healthy and SIRS horses were 18.28 ± 20.32 and 197.0 ± 117.0 pg/mL, respectively. T‐test showed statistical differences between healthy versus SIRS group and between healthy versus all subgroups. Conclusions and Clinical Importance: Results showed an increase in PCT concentration in SIRS horses as previously reported in humans and dogs. PCT could be used as a single assay in equine practice for detection of SIRS.